Influence of day and night temperature on the growth, development and yield of greenhouse sweet pepper - LI Guo-jing; Benoit F; Ceustermans N (浙江大学学报. 农业与生命科学版, 2004)
The objective of this experiment was to quantify vegetative and generative responses of sweet pepper plants to different day/night temperature regimes (DIF). Sweet pepper plants were grown on rockwool substrates in two glasshouses, in which two DIF, i. e. 20-16℃ (DIF +4 ℃) and 16-20℃ (DIF —4 ℃) were applied. Results showed that negative DIF significantly reduced the internode length and leaf size of pepper cv. Spirit plants, but no significant effect on leaf unfolding rate, earliness, yield or fruit quality was observed. Water consumption of pepper plants in DIF +4℃ consumed 31% more nutrient solution than those in DIF -4 ℃. Correspondently, the EC level of the drained solution from DIF +4℃ increased with the development of pepper plants. The pepper fruits cv. Spirit from negative DIF elongated much faster than that of positive DIF. The temperature fluctuation between day and night did not affect neither fruit external nor internal quality. Different varieties have different responses to DIF.